2020
DOI: 10.2196/18768
|View full text |Cite
|
Sign up to set email alerts
|

Learning Impact of a Virtual Brain Electrical Activity Simulator Among Neurophysiology Students: Mixed-Methods Intervention Study

Abstract: Background: Virtual simulation is the recreation of reality depicted on a computer screen. It offers the possibility to exercise motor and psychomotor skills. In biomedical and medical education, there is an attempt to find new ways to support students' learning in neurophysiology. Traditionally, recording electroencephalography (EEG) has been learned through practical hands-on exercises. To date, virtual simulations of EEG measurements have not been used. Objective: This study aimed to examine the development… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…They also benefited from the reflection they experienced. In a previous study, we found that EEG-simulator gave the greatest improvement in learning as assessed by pre-and post-test knowledge [4]. This met our expectations that the simulation focuses on Bloom's higher learning goals [25].…”
Section: Learning By Simulationsupporting
confidence: 76%
See 3 more Smart Citations
“…They also benefited from the reflection they experienced. In a previous study, we found that EEG-simulator gave the greatest improvement in learning as assessed by pre-and post-test knowledge [4]. This met our expectations that the simulation focuses on Bloom's higher learning goals [25].…”
Section: Learning By Simulationsupporting
confidence: 76%
“…Simulators have been seen to improve medical training, allowing users to interact in a virtual environment, increasing contact, for example. Simulations especially support learning of hands-on skills, but also theoretical knowledge as shown in previous studies [4,5]. Simulations provide a safe environment for students to practice the role of a registered health professional [6].…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…From the 92 published studies, VS was reported to be applied in the educational practice involving undergraduate medical students across 25 countries including the United States [26 studies ( 15 40 )], the United Kingdom [9 studies ( 41 49 )], Germany [7 studies ( 50 – 56 )], China [6 studies ( 10 , 57 61 )], Denmark [6 studies ( 62 – 67 )], France [4 studies ( 68 71 )], Japan [4 studies ( 72 75 )], Sweden [3 studies ( 76 78 )], Canada [3 studies ( 79 – 81 )], Netherlands [3 studies ( 82 84 )], Spain [3 studies ( 85 87 )], Australia [2 studies ( 88 , 89 )], Singapore [2 studies ( 90 , 91 )], Korea [2 studies ( 92 , 93 )], Finland [1 study ( 94 )], Italy [1 study ( 95 )], Ireland [1 study ( 96 )], Colombia [1 study ( 97 )], Pakistan [1 study ( 98 )], Thailand [1 study ( 99 )], Iran [1 study ( 100 )], Poland [1 study ( 101 )], Mexico [1 study ( 102 )], Norway [1 study ( 103 )], Saudi Arabia [1 study ( 104 )], and Switzerland [1 study ( 105 )]. The distribution of included studies among different continents was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%